2012
DOI: 10.1007/s10532-012-9611-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ferrihydrite on 2,4,6-trinitrotoluene biotransformation by an aerobic yeast

Abstract: This study investigated the impact of ferrihydrite on the pathway and rate of 2,4,6-trinitrotoluene (TNT) transformation by Yarrowia lipolytica AN-L15. The presence of ferrihydrite in the culture medium decreased the rate of TNT biotransformation but resulted in the accumulation of the same TNT metabolites as in the absence of ferrihydrite, albeit at slightly different concentrations. Transformation products observed included aromatic ring reduction products, such as hydride-Meisenheimer complexes, and nitro g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…Y. lipolytica removed TNT in the range of 63–82% of TNT during the first day of incubation, while the remaining 18–37% were further transformed in the following 3 to 4 days of the experiments. The TNT biotransformation by Y. lipolytica was slower compared to previous studies (Ziganshin et al 2010b ; Khilyas et al 2013 ), which can be explained by the lower initial yeast cell concentration used for these experiments (initial OD 600 of 0.05). When an initial OD 600 of 0.2 or 1.0 was used in Ziganshin et al ( 2010b ) and Khilyas et al ( 2013 ), TNT was completely removed in the absence of ferric (oxyhydr)oxides within 24 and 10 hours, respectively.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Y. lipolytica removed TNT in the range of 63–82% of TNT during the first day of incubation, while the remaining 18–37% were further transformed in the following 3 to 4 days of the experiments. The TNT biotransformation by Y. lipolytica was slower compared to previous studies (Ziganshin et al 2010b ; Khilyas et al 2013 ), which can be explained by the lower initial yeast cell concentration used for these experiments (initial OD 600 of 0.05). When an initial OD 600 of 0.2 or 1.0 was used in Ziganshin et al ( 2010b ) and Khilyas et al ( 2013 ), TNT was completely removed in the absence of ferric (oxyhydr)oxides within 24 and 10 hours, respectively.…”
Section: Resultsmentioning
confidence: 54%
“…In almost all cases TNT transformation in the presence of iron species is accompanied by the enhanced formation and accumulation of undesirable metabolites, such as hydroxylamino-dinitrotoluenes (HADNTs), amino-dinitrotoluenes (ADNTs) and/or diamino-nitrotoluenes (DANTs) (Hofstetter et al 1999 ; Borch et al 2005 ; Oh et al 2008 ; Boparai et al 2010 ), which are fairly persistent and approximately as toxic as TNT itself (Smets et al 2007 ; Khan et al 2013 ). Only a few studies have reported denitration of TNT in the presence of ferrihydrite (Eyers et al 2008 ; Khilyas et al 2013 ). In terms of the efficiency of remediation strategies, TNT denitration processes resulting in nitro group elimination would be advantageous if the nitro group reduction pathways could be minimized.…”
Section: Introductionmentioning
confidence: 99%
“…As the acidic HPLC conditions required to separate the isomeric reduction products also promoted rapid re-oxidation during handling, we sought to generate more stable,i solable derivatives required for more detailed structural analysis.W eanticipated that the dearomatized reduced products should be susceptible to reactions with electrophiles,w hich might provide derivatives suitable for detailed characterization. Meisenheimer complexes are known, [12] but are often unstable intermediates in nucleophilic substitution reactions of electron-poor aromatic systems.O nly few examples have been identified in biological systems,f or example,inthe biodegradation of explosives such as TNT by Yarrowia lipolytica [13] and other nitroaromatic compounds. Consistent with generation of aM eisenheimer complex, the NMR spectrum of each isomer (6a, b)featured only one low-field proton (7.0 and 7.3 ppm, respectively) and an ew upfield signal (3.7 and 3.5 ppm, respectively), which was later shown to be am ethylene group by DEPT135 measurements.These data unequivocally showed that the reduction of BTZ043 occurs at the aromatic core,a nd that the two products (6a, b or 5a, b)a re regioisomers of ah ydride Meisenheimer complex (Figure 2A).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Consistent with generation of aM eisenheimer complex, the NMR spectrum of each isomer (6a, b)featured only one low-field proton (7.0 and 7.3 ppm, respectively) and an ew upfield signal (3.7 and 3.5 ppm, respectively), which was later shown to be am ethylene group by DEPT135 measurements.These data unequivocally showed that the reduction of BTZ043 occurs at the aromatic core,a nd that the two products (6a, b or 5a, b)a re regioisomers of ah ydride Meisenheimer complex (Figure 2A). Meisenheimer complexes are known, [12] but are often unstable intermediates in nucleophilic substitution reactions of electron-poor aromatic systems.O nly few examples have been identified in biological systems,f or example,inthe biodegradation of explosives such as TNT by Yarrowia lipolytica [13] and other nitroaromatic compounds. [14] However,tothe best of our knowledge,transformations that afford Meisenheimer complexes in vivo have not been described for any drug or drug candidate.T he installation of the methyl group in 6a, b also allowed assignment of the regiochemistry of both isomers through ac ombination of NOESY and HMBC coupling studies ( Figure 2B).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In aquatic systems, explosives undergo extensive abiotic and microbial transformation and degradation processes (Khilyas et al 2013;Boopathy 2014;. Bioremediation techniques are commonly used in the degradation of different pollutants, including nitrocellulose, since they allow producing environmentally safe transformation products at potentially lower costs compared to physicochemical treatment processes (El-Diwani et al 2009;Giacomucci et al 2012).…”
Section: Introductionmentioning
confidence: 99%